Genetic similarity analysis within Pyropia yezoensis blades developed from both conchospores and blade archeospores using AFLP1. Issue 3 (21st March 2013) - He, Linwen; Zhu, Jianyi; Lu, Qinqin; Niu, Jianfeng; Zhang, Baoyu; Lin, Apeng; Wang, Guangce; Cock, M.
<x xml:space="preserve">Abstract</x> Pyropia yezoensis (Ueda) M. S. Hwang et H. G. Choi (previously called Porphyra yezoensis) is an economically important alga. The blades generated from conchospores are genetic chimeras, which are not suitable for genetic similarity analysis. In this study, two types of blades from a single filament of P. yezoensis sporophyte filament were obtained. One type, ConB, consisted of 40 blades that had germinated from conchospores. The other type, ArcB, consisted of 88 blades that had germinated from archeospores released from ConB. Both of them were analyzed by amplified fragment length polymorphism. The low genetic similarity levels for both conchospore‐germinated and archeospore‐germinated blades demonstrated that the conchcelis we used was cross‐fertilized. Furthermore, a higher polymorphic loci ratio (98.6%) was detected in ArcB than in ConB (80.7%), and the average genetic similarity of ArcB (average 0.61) was lower than that of ConB (average 0.71). These differences indicated that genetic analysis using ArcB gives more accurate results.